Pengelolaan sumberdaya perikanan rawa gambut untuk meningkatkan perekonomian masyarakat Desa Tanjung Taruna Kabupaten Pulang Pisau - Shinta P. Yuptriani; Muhammad Rizal; Agung Prasetyo; Riza Fahlifi; Josua Situmorang; Dhea Rahmadini; Enrico Rafael Siahaan; Deden Priyatna Sumantri; Megawati Sinambela; Rossyta Aprilyani; Achmad Faried Rindhianto; Kevin Agus Trianto; Wendi Setiawan; Dewi Anggrieni; Sri Endang Agustina Rahayuningsih (Unri Conference Series: Community Engagement, 2020)
Tanjung Taruna Village is one of the areas in Jabiren Raya Subdistrict, Pulang Pisau Regency, Central Kalimantan province. This village is included in the peat swamp area and the Kahayan river basin. This village is geographically located in a watershed, making fishery products abundant, but the local community is constrained by marketing and processing fishery resources. Most of the population works as fishermen. This Village Development Grant Program (PHBD) activity aims to provide training and assistance to increase knowledge, skills and community welfare. The method of activity is carried out by conducting socialization, training and mentoring on the processing of fish into shredded and meatball products in order to increase the sale value of these fish which previously were only sold in the form of fresh fish and salted fish. The results of the activity showed that the participation of the participants was quite good with 38 participants. Based on the results of the training evaluation, it is known that 95.5% of the training participants have increased knowledge and can process fish products from their natural resources to be processed into fish balls and fish floss can be used as a source of household income.